Fiber composite thermal closed pore diaphragm and preparation method and application thereof

By using fibrous composite thermal closed -hole diaphragm, using the composite technique of high temperature resistance and low -melting point function fibers solves the problem of heat -lost control in the battery in high temperature environments, realize the safety performance and cycle stability of the battery, while increasing the charging at the same time Efficiency of discharge.

CN119361964APending Publication Date: 2025-01-24DONGHUA UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411317263.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing lithium-ion and sodium-ion batteries are prone to thermal runaway in the case of short circuit, overcharging, overheating or high-speed charging, resulting in safety risks of combustion or explosion. The commercial diaphragm has uneven pores, low mechanical strength, and poor thermal stability. It is difficult to effectively improve the safety performance and cycle stability of the battery.

Method used

The fiber composite thermal obturator separator is used to mix high-temperature resistant organic functional fibers and low-melting functional fibers in different proportions, and add dispersants for dispersion to form a composite fiber dispersion, which is obtained through film formation, drying and rolling processes. Fiber composite thermal closed cell separator. The separator has a thermal obturator effect under thermal runaway, blocking the conduction of lithium ions and improving the safety performance of the battery. It also has high ion conductivity, reduces the internal resistance of the battery, and improves charge and discharge efficiency and stability.

Benefits of technology

It effectively prevents the risk of short circuit and combustion caused by thermal runaway of the battery, improves the safety performance and cycle stability of the battery, while reducing the internal resistance of the battery and improving the charging and discharging efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361964A_ABST
    Figure CN119361964A_ABST
Patent Text Reader

Abstract

The invention relates to a fiber composite thermal closed pore diaphragm and a preparation method and application thereof. The fiber composite diaphragm has high-temperature stability, and the thermal closed pore characteristic can block ion conduction, so that thermal runaway of a battery is effectively avoided, and the safety performance of the battery is effectively improved; meanwhile, the thermal closed pore functional fiber diaphragm has high ionic conductivity, the ionic conductivity refers to the conduction capability of ions in electrolyte, and the high ionic conductivity is beneficial to reducing the internal resistance of the battery, improving the conduction efficiency of current, reducing the energy loss and improving the charge-discharge efficiency and the stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery separators, and in particular relates to a fiber composite thermal closed-cell separator and a preparation method and application thereof. Background Art

[0002] With the continuous increase in the power consumption time of mobile electronic devices (such as smartphones, laptops, etc.) and the rapid development of high-power consumption devices such as drones and electric vehicles, battery energy storage devices have ushered in new challenges. In energy storage systems, lithium-ion batteries are widely used due to their high energy density and good cycle stability. The rapid development of the electronics industry has intensified the demand for large-capacity power sources, resulting in cost problems due to the excessive application of lithium-ion batteries. Therefore, sodium batteries have been developed as a new generation of battery energy storage technology.

[0003] As battery energy density increases, battery safety issues are increasingly attracting attention. Lithium-ion and sodium-ion batteries will release a large amount of heat in a short period of time when short-circuited, overcharged, overheated, or charged at a high rate. The local temperature rises sharply. If the heat cannot be dissipated quickly, there will be safety risks of combustion or even explosion. The diaphragm is one of the essential internal components of energy storage batteries. It determines the interface structure and internal resistance of the battery, and directly affects the battery capacity, cycle and safety performance. Commercial polypropylene and polyethylene diaphragms have the disadvantages of large and uneven pore size (hundreds of nanometers), low mechanical strength (less than 10MPa), low ionic conductivity, and poor thermal stability, which can easily cause internal short circuits and thermal runaway problems. Glass fiber has high mechanical strength and can withstand temperatures up to 550°C, but it has disadvantages such as poor bending resistance and has not been commercially applied on a large scale. Modification methods such as physical coating and chemical modification of the surface of the separator can inhibit lithium dendrites to a certain extent and improve the thermal stability of the battery, but there are problems such as blocking the pores of the separator, destroying the microstructure of the separator, complex operating process, high cost, environmental pollution, and shedding of the surface modification layer.

[0004] CN 109817867A discloses a thermosensitive coating material, a thermosensitive diaphragm, and a preparation method and application thereof; the thermosensitive coating material comprises the following components in percentage by mass: 3-10% of a polymer binder, 80-90% of an inorganic metal oxide, 0.5-1% of a dispersant, and 5-15% of heat-expandable polymer microspheres; the thermosensitive diaphragm prepared from the thermosensitive coating material enables the battery to have higher safety performance during overcharging and better structural stability.

[0005] CN 111785893A discloses a coated polypropylene diaphragm with a low closed-cell temperature, comprising: a porous polypropylene diaphragm substrate and a closed-cell coating coated on at least one surface of the polypropylene diaphragm substrate; wherein the raw materials of the closed-cell coating include, by weight percentage: 80-95wt% of a thermoplastic microsphere emulsion and 5-20wt% of an aqueous binder; it has a lower closed-cell temperature and a higher membrane rupture temperature, can effectively prevent the occurrence of thermal runaway of a lithium-ion battery, and significantly improve the safety of the lithium-ion battery.

[0006] However, the thermosensitive layer coating film in the above prior art has the disadvantages of large thickness, poor air permeability, poor liquid retention capacity and high heat shrinkage resistance, which is not conducive to improving the battery cycle stability and electrochemical interface regulation performance, nor is it conducive to industrial production; therefore, it is urgent to develop a high-temperature functional fiber thermal closed-cell diaphragm. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a fiber composite thermal closed-cell diaphragm and its preparation method and application. The diaphragm of the present invention has a thermal closed-cell effect under thermal runaway, blocks the conduction of lithium ions, effectively protects the battery from the influence of thermal accidents, prevents battery short circuit caused by continuous temperature increase, and effectively improves the safety performance of energy storage batteries; at the same time, the thermal closed-cell functional fiber diaphragm has high ionic conductivity, which refers to the conduction ability of ions in the electrolyte. High ionic conductivity helps to reduce the internal resistance of the battery, improve the conduction efficiency of the current, reduce energy loss, and improve the charging and discharging efficiency and stability of the battery.

[0008] The present invention provides a method for preparing a fiber composite thermal closed-cell diaphragm with simple process and scalability, and the prepared diaphragm has stable parameters, comprising:

[0009] (1) Determine the ratio of high temperature resistant organic functional fiber and low melting point functional fiber and the preparation of composite fiber dispersion:

[0010] The high temperature resistant organic functional fiber and the low melting point functional fiber are mixed in different proportions to obtain short fibers in different proportions, and then a dispersant is added to disperse the fibers to obtain a dispersion;

[0011] (2) Fiber composite thermal closed-cell diaphragm molding process and post-processing:

[0012] The dispersion in step (1) is prepared into a film, which is then dried and rolled to obtain a fiber composite thermal closed-cell diaphragm.

[0013] Preferably, the average diameter of the high temperature resistant organic functional fiber in step (1) is 0.1-5 μm, and the heat deformation temperature of the high temperature resistant organic functional fiber is ≥200°C; further preferably, the heat deformation temperature of the high temperature resistant organic functional fiber is 200°C-600°C.

[0014] Preferably, the low-melting-point functional fiber has an average diameter of 0.1-5 μm, and the continuous use temperature of the low-melting-point functional fiber is ≤150°C. More preferably, the continuous use temperature of the low-melting-point functional fiber is 60°C-180°C.

[0015] Preferably, the high temperature resistant organic functional fiber in step (1) comprises one or more of para-aramid PPTA fiber, polyphenylene sulfide PPS fiber, polyimide PI fiber, polyetheretherketone PEEK fiber, polytetrafluoroethylene PTFE fiber, polyparaphenylene benzobisoxazole PBO fiber, and poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole PIPD fiber;

[0016] Preferably, the low melting point functional fiber includes one or more of polyethylene PE fiber, polypropylene PP fiber, high density polyethylene HDPE fiber, and cellulose fiber.

[0017] Preferably, in the step (1), the high temperature resistant functional organic fiber is pretreated; the low melting point functional fiber is pretreated to obtain the pretreated high temperature resistant organic functional fiber and the pretreated low melting point functional fiber;

[0018] Preferably, the pretreatment is: cutting the fibers (high temperature resistant organic functional fibers, low melting point functional fibers), adding them into an organic solution for ultrasonic cleaning, taking out the ultrasonically cleaned fibers and rinsing them with water, and then air drying; wherein the mass of the high temperature resistant organic functional fibers is ≥0.5g; the mass of the low melting point functional fibers is ≥0.5g; and the cutting length is less than 3cm.

[0019] Preferably, the cutting length of the fiber is 0.2cm-3cm; the organic solution is an acetone solution; the power of the ultrasonic cleaning is ≥100W, and the cleaning time is ≥1h; the water is deionized water; the water flushing is deionized water cleaning for no less than 3 times, and the duration of each cleaning is ≥15min; the air drying time is more than 20h to completely remove moisture from the fiber.

[0020] Furthermore, the pretreatment includes: cutting the fibers, adding them to an acetone solution, placing them in an ultrasonic cleaner for ultrasonic cleaning, taking out the ultrasonically cleaned fibers and repeatedly rinsing them with deionized water, and then placing them in a blast drying oven for blast drying to obtain dry short fibers.

[0021] Preferably, in step (1), the mass ratio of the high temperature resistant organic fiber to the low melting point functional fiber is 1:1-100:1; and the amount of the dispersant added is 0.1%-2% of the total mass of the fiber.

[0022] Furthermore, the mass ratio of the untreated or pretreated high temperature resistant organic functional fiber to the untreated or pretreated low melting point functional fiber is 1:1-100:1;

[0023] Further preferably, the mass ratio of the high temperature resistant organic functional fiber to the low melting point functional fiber is 1:1-30:1.

[0024] The mass ratio of the untreated or pretreated high-temperature resistant organic functional fiber to the untreated or pretreated low-melting-point functional fiber is 1:1-30:1.

[0025] Preferably, the dispersant in step (1) is one or more of a water-soluble polymer dispersant and a surfactant; wherein the water-soluble polymer dispersant includes one or more of polyethylene oxide and polyacrylamide; and the surfactant includes one or more of sodium dodecyl sulfate and carboxymethyl cellulose.

[0026] Preferably, the dispersion in step (1) is performed by beating and dispersing for 0.5 h to 8 h, wherein the beating and dispersing is performed by uniformly dispersing in a beating machine.

[0027] Preferably, the film forming in step (2) is wet film forming; wherein the wet film forming is performed in a wet forming device.

[0028] Preferably, in the step (3), the drying temperature is below 100° C. and the drying time is below 48 h; the rolling temperature is below 180° C. and the rolling pressure is 0 MPa-30 MPa.

[0029] Further preferably, in the step (2), the drying temperature is 30°C-80°C, and the drying time is 12h-48h; and the rolling temperature is 25°C-180°C.

[0030] In step (2), the rolling is followed by cutting.

[0031] The invention provides a fiber composite thermal closed-cell diaphragm prepared by the method.

[0032] The present invention provides an application of the fiber composite thermal closed-cell diaphragm in an energy storage battery, wherein the energy storage battery includes at least one of a lithium ion battery (LIB), a lithium sulfur battery (LSB), a sodium ion battery (SIB), a zinc ion battery (ZIB), etc.

[0033] The present invention obtains a fiber composite thermal closed-cell diaphragm by selecting high-temperature resistant organic functional fibers and low-melting-point functional fibers, fiber pretreatment, fiber composite thermal closed-cell diaphragm molding process and post-treatment. The fiber composite diaphragm obtained based on this preparation method can enhance the mechanical properties and ionic conductivity of the diaphragm; at the same time, it has a high-temperature thermal shutdown function, and under the premise of ensuring the safe operation of the battery, by regulating the interface, the growth of dendrites is inhibited, thereby improving the battery cycle stability.

[0034] Beneficial Effects

[0035] The purpose of the present invention is to provide a high-temperature functional fiber thermal closed-cell diaphragm and a preparation method and application thereof. The fiber composite thermal closed-cell diaphragm obtained by the preparation method has a high-temperature thermal shutdown function, thereby improving the safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a photo of the fiber composite thermal closed-cell diaphragm prepared in Example 1;

[0037] Figure 2 This is a photo of the fiber composite thermal closed-cell diaphragm prepared in Example 3;

[0038] Figure 3 This is a photo of the fiber composite thermal closed-cell diaphragm prepared in Example 5;

[0039] Figure 4 The impedance test of the fiber composite thermal closed-cell diaphragm prepared as described in Examples 1 and 2;

[0040] Figure 5 The impedance test of the fiber composite thermal closed-cell diaphragm prepared as described in Examples 3 and 4;

[0041] Figure 6 The impedance test of the fiber composite thermal closed-cell diaphragm prepared as described in Examples 5 and 6;

[0042] Figure 7 This is a photo of the high-temperature resistant organic functional fiber membrane prepared in comparative example 1. DETAILED DESCRIPTION

[0043] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0044] Example 1

[0045] PPS fiber was taken as high-temperature resistant organic functional fiber, and PP fiber was taken as low-melting-point functional fiber. The average diameter of the selected fiber was 200 nm. The fiber was cut into 1 cm short fibers and added into acetone solution. It was placed in an ultrasonic cleaner for ultrasonic cleaning for 1 hour. The ultrasonically cleaned fiber was taken out and rinsed repeatedly with deionized water for 3 times, each time for 15 minutes. It was then placed in a blast drying oven for blast drying. After drying for 20 hours, dry short fibers were obtained.

[0046] The pretreated high-temperature resistant organic functional fiber and the low-melting-point functional fiber were weighed, mixed at a mass ratio of 6:1, added into water, and 0.5% of the total mass of the fiber polyacrylamide dispersant was added, and uniformly dispersed in a beater for 8 hours.

[0047] The composite short fiber dispersion was transferred to the wet forming equipment for film formation. After the film forming process was completed, the fiber composite thermal closed-cell diaphragm was dried at 30°C for 12 hours; then the fiber composite thermal closed-cell diaphragm was rolled at 50°C and 0MPa, and the diaphragm was cut and left to stand at 180°C for 24 hours before testing its impedance. Figure 1 The impedance diagram is shown as Figure 4 The button cell was assembled in a glove box filled with argon gas, where H 2 O and O 2 The content of is lower than 0.1ppm. The electrolyte is composed of DOL (1,3-dioxolane) and DME (1,2-dimethoxyethane) (1:1, volume ratio), with 1M LiTFSI and 0.1M LiNO 3 The impedance test is to assemble the separator in a 2032 standard button cell, and use it in the potential range of 1.7 to 2.8V (compared with Li / Li+), and evaluate the impedance of the battery through the EIS test on the Coster electrochemical workstation, and then calculate the ionic conductivity of the battery to be 1.77×10 -4 S cm -2 .

[0048] Example 2

[0049] On the basis of Example 1: the average diameter of the selected fiber is 200 nm, the pre-treated high temperature resistant organic functional fiber and the low melting point functional fiber are weighed and mixed at a mass ratio of 6:1, and 0.5% of the total mass of the fiber polyacrylamide dispersant is added, and the mixture is evenly dispersed in a beater for 8 hours. After the separator is cut and left to stand at 185°C for 24 hours, its impedance is tested, and the ionic conductivity of the battery is calculated to be 8.58×10 -5 S cm -2 , the rest is the same as in Example 1, the impedance diagram is as follows Figure 4 shown.

[0050] Example 3

[0051] On the basis of Example 1: the average diameter of the selected fiber is 200 nm, the pre-treated high temperature resistant organic functional fiber and the low melting point functional fiber are weighed and mixed at a mass ratio of 5:1, and 1% of the total mass of the fiber polyacrylamide dispersant is added, and the mixture is evenly dispersed in a beater for 12 hours. After the separator is cut and left to stand at 175°C for 24 hours, its impedance is tested, and the ionic conductivity of the battery is calculated to be 4.87×10 -5 S cm -2 , the rest is the same as in Example 1, the actual picture of the diaphragm is as follows Figure 2 The impedance diagram is shown as Figure 5 shown.

[0052] Example 4

[0053] On the basis of Example 1: the average diameter of the selected fiber is 200 nm, the pre-treated high temperature resistant organic functional fiber and the low melting point functional fiber are weighed and mixed at a mass ratio of 5:1, and 1% of the total mass of the fiber polyacrylamide dispersant is added, and the mixture is evenly dispersed in a beater for 12 hours. After the separator is cut and left to stand at 185°C for 24 hours, its impedance is tested, and the ionic conductivity of the battery is calculated to be 2.94×10 -5 S cm -2 , the rest is the same as in Example 1, the impedance diagram is as follows Figure 5 shown.

[0054] Example 5

[0055] On the basis of Example 1: the average diameter of the selected fiber is 200 nm, the pre-treated high temperature resistant organic functional fiber and the low melting point functional fiber are weighed and mixed at a mass ratio of 4:1, and 1% polyacrylamide dispersant of the total mass of the fiber is added, and the fiber composite thermal closed-cell diaphragm is evenly dispersed in a beater for 12 hours, and the fiber composite thermal closed-cell diaphragm is dried at a drying temperature of 50°C and a drying time of 24 hours. After the diaphragm is cut and left to stand at 175°C for 24 hours, its impedance is tested, and the ionic conductivity of the battery is calculated to be 5.12×10 -5 S cm -2 , the rest is the same as in Example 1, the actual picture of the diaphragm is as follows Figure 3 The impedance diagram is shown as Figure 6 shown.

[0056] Example 6

[0057] On the basis of Example 1: the average diameter of the selected fiber is 200 nm, the pre-treated high temperature resistant organic functional fiber and the low melting point functional fiber are weighed and mixed at a mass ratio of 4:1, and 1% polyacrylamide dispersant of the total mass of the fiber is added, and the fiber composite thermal closed-cell diaphragm is evenly dispersed in a beater for 12 hours, and the fiber composite thermal closed-cell diaphragm is dried at a drying temperature of 50°C and a drying time of 24 hours. After the diaphragm is cut and left to stand at 180°C for 24 hours, its impedance is tested, and the ionic conductivity of the battery is calculated to be 4.78×10 -5 S cm -2 , the rest is the same as in Example 1, the impedance diagram is as follows Figure 6 shown.

[0058] Example 7

[0059] On the basis of Example 1: the average diameter of the selected fiber is 200nm, the pre-treated high-temperature resistant organic functional fiber and the low-melting point functional fiber are weighed and mixed at a mass ratio of 15:1, and 1% polyacrylamide dispersant of the total fiber mass is added, and the mixture is evenly dispersed in a beater for 12 hours. The rolling temperature of the fiber composite thermal closed-cell diaphragm is 30°C, and the rolling pressure is 0MPa. After the diaphragm is cut, it is allowed to stand at 185°C for 24 hours and then its impedance is tested. The rest is the same as Example 1.

[0060] Example 8

[0061] On the basis of Example 1: the average diameter of the selected fiber is 200nm, the pre-treated high-temperature resistant organic functional fiber and the low-melting point functional fiber are weighed and mixed at a mass ratio of 15:1, and 1% polyacrylamide dispersant of the total fiber mass is added, and the mixture is evenly dispersed in a beater for 8 hours. The rolling temperature of the fiber composite thermal closed-cell diaphragm is 30°C, and the rolling pressure is 5MPa. After the diaphragm is cut, it is allowed to stand at 185°C for 24 hours and then its impedance is tested. The rest is the same as Example 1.

[0062] Example 9

[0063] On the basis of Example 1: the selected fiber diameter is 0.5-10 μm, the pre-treated high temperature resistant organic functional fiber and the low melting point functional fiber are weighed and mixed at a mass ratio of 15:1, and 1% of the total fiber mass of polyacrylamide dispersant is added, and the fiber composite thermal closed cell diaphragm is rolled at a temperature of 30°C and a rolling pressure of 15 MPa, and the diaphragm is cut and left to stand at 185°C for 24 hours before testing its impedance. The rest is the same as Example 1.

[0064] Comparative Example 1

[0065] Only PPS fiber was taken as the high-temperature resistant organic functional fiber. The average diameter of the selected fiber was 200 nm. The fiber was cut into 1 cm short fibers and added into an acetone solution. It was placed in an ultrasonic cleaner for ultrasonic cleaning for 1 hour. The ultrasonically cleaned fiber was taken out and rinsed repeatedly with deionized water for 3 times, each time for 15 minutes. It was then placed in a blast drying oven for blast drying. After drying for 20 hours, dry short fibers were obtained.

[0066] 0.5 g of the pretreated high-temperature resistant organic functional fiber was added into water, and 0.5% of the total weight of the fiber was added as a polyacrylamide dispersant, and the mixture was evenly dispersed in a beater for 8 hours.

[0067] The high temperature resistant organic functional fiber dispersion was transferred to a wet forming device for film formation. After the film forming process was completed, the high temperature resistant organic functional fiber membrane was dried at 30°C for 12 hours. Thereafter, the high temperature resistant organic functional fiber membrane was rolled at 50°C and 0MPa. After the membrane was cut, it was left to stand at 25°C for 24 hours. The actual picture is as follows: Figure 7 As shown, the diaphragm has not formed closed cells and still has a relatively loose structure, which cannot ensure the safety of the diaphragm.

[0068] Comparative Example 2

[0069] Only PP fiber low-melting point functional fiber is taken, the average diameter of the selected fiber is 200nm, the fiber is cut into 1cm short fiber, added into acetone solution, put into ultrasonic cleaner for ultrasonic cleaning for 1h, take out the ultrasonically cleaned fiber and rinse it repeatedly with deionized water for 3 times, each time for 15min, then put it into a blast drying oven for blast drying, and obtain dry short fiber after drying for 20h.

[0070] 0.5 g of the pretreated high-temperature resistant organic functional fiber was added into water, and 0.5% of the total weight of the fiber was added as a polyacrylamide dispersant, and the mixture was evenly dispersed in a beater for 8 hours.

[0071] The PP fiber low-melting point functional fiber dispersion was transferred to a wet molding device for film formation. After the film formation process was completed, the low-melting point functional fiber membrane was dried at 30°C for 12 hours; then the low-melting point functional fiber membrane was rolled at 50°C and 0MPa, and the membrane was cut and left to stand at 25°C for 24 hours. The prepared low-melting point functional fiber membrane was completely dense after rolling without any gaps, and could not meet the basic structural conditions of the battery membrane.

[0072] Depend on Figure 1-3It can be seen that the prepared microporous fiber composite diaphragm has uniform pores, and due to the inherent properties of the fiber, the diaphragm has a thermal closure effect under thermal runaway, blocking the conduction of lithium ions, and effectively protecting the battery from thermal accidents; preventing battery short circuit caused by continuous temperature increase, thereby improving the cycle life and safety performance of the energy storage battery; at the same time, the thermally closed-cell functional fiber diaphragm has high ionic conductivity. Ionic conductivity refers to the conduction ability of ions in an electrolyte. High ionic conductivity helps to reduce the internal resistance of the battery, improve the conduction efficiency of current, reduce energy loss, and improve the charging and discharging efficiency and stability of the battery.

[0073] Depend on Figure 4-6 It can be seen that the impedance of the fiber composite thermal closed-cell diaphragm increases significantly under high temperature environment, indicating that the melting of the low-melting-point functional fiber blocks the pore structure of the high-temperature resistant organic functional fiber, so that the prepared microporous fiber composite diaphragm has a high-temperature thermal shutdown function, thereby improving the safety performance of the battery.

Claims

1. A method for preparing a fiber composite thermal closed-cell diaphragm, comprising: (1) mixing high temperature resistant functional organic fiber and low melting point functional fiber, and then adding water and dispersant to disperse them to obtain a dispersion; (2) The dispersion in step (1) is formed into a film, and then dried and rolled to obtain a fiber composite thermal closed-cell diaphragm.

2. The preparation method according to claim 1, characterized in that: In the step (1), the heat deformation temperature of the high temperature resistant functional organic fiber is ≥200°C; the melting point of the low melting point functional fiber is ≤180°C.

3. The preparation method according to claim 1, characterized in that: The high temperature resistant organic functional fiber in step (1) includes one or more of para-aramid PPTA fiber, polyphenylene sulfide PPS fiber, polyimide PI fiber, polyetheretherketone PEEK fiber, polytetrafluoroethylene PTFE fiber, polyparaphenylene benzobisoxazole PBO fiber, and poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole PIPD fiber; The low melting point functional fiber includes one or more of polyethylene PE fiber, polypropylene PP fiber, high density polyethylene HDPE fiber, and cellulose fiber.

4. The preparation method according to claim 1, characterized in that: In the step (1), the high temperature resistant functional organic fiber is pretreated; and the low melting point functional fiber is pretreated.

5. The preparation method according to claim 4, characterized in that: The pretreatment comprises cutting the fiber, adding the fiber into an organic solution for ultrasonic cleaning, taking out the ultrasonically cleaned fiber, washing it with water, and then drying it with air blast; The cutting length of the fiber is less than 3 cm; the organic solution is an acetone solution; the water is deionized water; and the air drying time is more than 20 hours.

6. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of the high temperature resistant organic fiber to the low melting point functional fiber is 1:1-100:1; and the added amount of the dispersant is 0.1%-2% of the total mass of the fiber.

7. The preparation method according to claim 1, characterized in that: The dispersant in step (1) is one or more of a water-soluble polymer dispersant and a surfactant; the water-soluble polymer dispersant includes one or more of polyethylene oxide and polyacrylamide; the surfactant includes one or more of sodium dodecyl sulfate and carboxymethyl cellulose; the dispersion is a pulping dispersion for 0.5h-8h.

8. The preparation method according to claim 1, characterized in that: The film forming in step (2) is wet film forming; the drying temperature is below 100° C. and the time is below 48 h; the rolling temperature is below 180° C. and the rolling pressure is 0 MPa-30 MPa.

9. A fiber composite thermal closed-cell diaphragm prepared by the method of claim 1.

10. Use of the fiber composite thermal closed-cell diaphragm according to claim 9 in energy storage batteries.

Citation Information

Patent Citations

  • Thermo-sensitive coating material, thermo-sensitive diaphragm and preparation method and application of thermo-sensitive diaphragm

    CN109817867A

  • Coated polypropylene diaphragm with low pore closing temperature and preparation method thereof

    CN111785893A